Determination of pure and adulterated stingless bee honey based on dielectric properties - Sapri, Nur Shafiqah; Jamaludin, Diyana (Malaysian Society of Agricultural Engineers, 2019)
Recently, honey has become the target of adulteration due to high consumers demand and its nutritional value. This study was carried out to quantify adulteration of stingless bee (kelulut) honey from Heterotrigona Itama sp. based on its dielectric properties by using Precision Impedance Analyzer at frequency range of 40kHz to 40MHz. Five treatments of honey were prepared: 1) pure honey,2) adulterated with 15% water, 3) adulterated with 30% water, 4) adulterated with 15% sucrose and 5) adulterated with 30% sucrose. Result shows that dielectric constant (ε ′) decrease as frequency increase and the best frequency to distinguished between pure and adulterated honey is at the range of 10MHz to 40MHz. It was found that as percentage of sucrose added in pure honey increased, the dielectric constant is decreased while as the percentage of water added in pure honey increased, the dielectric constant is increased. Strong negative relationship was found between dielectric constant with viscosity (R2= 0.94), moisture content (R2= 0.98) and soluble solid content (R2= 0.81) at frequency of 40 MHz. From this result, it concludes that the dielectric properties of stingless bee honey can be used to differentiate between pure and adulterated honey and to determine viscosity, moisture content and soluble solid content of stingless bee honey.